AI-ASSISTED CROSS-CULTURAL ANALYSIS OF PHRASEOLOGICAL UNITS DENOTING HUMAN INTELLECTUAL ABILITIES - Gulchexra Tursunova Norboboyevna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study investigates the role of artificial intelligence in the cross-cultural analysis of phraseological units denoting human intellectual abilities, focusing on English and Uzbek languages. The research explores how AI-based translation tools interpret culturally bound idioms and whether they preserve semantic and cultural meanings. Using a dataset of 16 phraseological units, the study compares human interpretation with AI-generated translations. The findings reveal that while AI systems successfully translate literal meanings, they often fail to capture cultural nuances embedded in idiomatic expressions. The results highlight the importance of integrating cultural and cognitive linguistic knowledge into AI systems for more accurate translation and interpretation.